KARAKTERISTIK LAVA DAN KEMUNGKINAN PEMANFAATANNYA SEBAGAI BAHAN GALIAN KONSTRUKSI DAERAH MALIMPING KABUPATEN BANDUNG, JAWA BARAT - Sukiyah, Emi (Fakultas Teknik Geologi Universitas Padjadjaran, 2005)
This research background are potency and limitation aspects in construction material resourcesapplication in southern part of Bandung Regency. The problem of research is role of lava characteristicin application designe as construction material resources. This research use deduction method withprobabilityapproach. Result of research show lava at Malimping area and surrounding have characteristicare grey-black, fine to intermediate texture, basaltic. A part of lava has sheeting joint and anothermassive. Based on petrographic analysis, a part of lava has a little alteration. That condition showed bya part of pyroxene had altered to chlorite. Result of chemical and physical analysis of rock show lava atMalimping area and surrounding is basalt. Potency of lava at Malimping is significane as contructionmaterial. Based on morphometry calculation and lava outcrop spreading, lava potency estimated44.573.500 m3. Nevertheless, that all potency can’t used because it spread in upper area of Citarumriver. Based on lava characteristics, outcrop position, regulation of landuse and trend of communityneed so that basalt lava potency used as dimention stone. That using can up value of contructionmaterial so that income of community in that surrounding area can up too.